Presence of Inhibitory Glycinergic Transmission in Medium Spiny Neurons in the Nucleus Accumbens - Muñoz, Braulio; Yevenes, Gonzalo E.; Förstera, Benjamin; Lovinger, David M.; Aguayo, Luis G. (Frontiers in Molecular Neuroscience, 2018)
It is believed that the rewarding actions of drugs are mediated by dysregulation of the mesolimbic dopaminergic system leading to increased levels of dopamine in the nucleus accumbens (nAc). It is widely recognized that GABAergic transmission is critical for neuronal inhibition within nAc. However, it is currently unknown if medium spiny neurons (MSNs) also receive inhibition by means of glycinergic synaptic inputs. We used a combination of proteomic and electrophysiology studies to characterize the presence of glycinergic input into MSNs from nAc demonstrating the presence of glycine transmission into nAc. In D1 MSNs, we found low frequency glycinergic miniature inhibitory postsynaptic currents (mIPSCs) which were blocked by 1 µM strychnine (STN), insensitive to low (10, 50 mM) and high (100 mM) ethanol (EtOH) concentrations, but sensitive to 30 µM propofol. Optogenetic experiments confirmed the existence of STN-sensitive glycinergic IPSCs and suggest a contribution of GABA and glycine neurotransmitters to the IPSCs in nAc. The study reveals the presence of glycinergic transmission in a non-spinal region and opens the possibility of a novel mechanism for the regulation of the reward pathway.